Styling the Self: Clothing Practices, Personality Traits, and Body Image Among Israeli Women - Stolovy, Tali (Frontiers in Psychology, 2021)
Research has shown that women tend to use clothes to present or disguise their bodies and that clothing practices can be predicted by body image. This study explored the relationships between clothing practices, personality traits, and body image among Israeli women, using the Big Five personality traits model (NEO-FFI; Costa & McCrae, 1992) and a body image measure (MBSRQ, Cash, 1994) to explore clothing styles and practices among Israeli women (N= 792, Mean age = 42.19). It found that women with are more openness to experience (OR = 1.8; IC 95%: 1.05-3.0), who seek fashion (OR = 2.05; IC 95%: 1.37-3.05) and individuality (OR = 3.96; IC 95%: 2.46-6.3) are more likely to exhibit a urban, sophisticated style of dress. These women are less motivated by comfort (OR = 0.49; IC 95%: 0.31-0.77) and camouflage (OR = 2.05; IC 95%: 1.37-3.05), that are associated with casual, minimalist style of dress. This study indicates that openness to experience may foster body-positive clothing practices. In this way, their choice of clothing can help women overcome objectification and cultural body-ideal pressures, promoting self-validation and mastery.